2012
DOI: 10.1007/s12640-012-9326-7
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Nicotine Against Aminochrome-Induced Toxicity in Substantia Nigra Derived Cells: Implications for Parkinson’s Disease

Abstract: Parkinson’s disease is a debilitating progressive neurodegenerative disorder that results from the loss of or damage to dopaminergic cells containing neuromelanin in the substantia nigra (SN). The underlying neurodegenerative mechanism(s), however, remain elusive. Aminochrome, the precursor of neuromelanin is an endogenous substance capable of inducing selective neurotoxicity to dopaminergic neurons in SN. Nicotine, on the other hand, may offer protective effects against dopaminergic cell damage induced by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…In-vivo and in-vitro studies have shown that nicotine protects against nigrostriatal damage induced by various compounds. For example, in Parkinson's disease cell models nicotine protects against endogenous substances such as salsolinol and aminochrome that selectively damage dopaminergic cells (Copeland et al 2005, 2007; Das and Tizabi 2009; Muñoz et al 2012; Ramlochansingh et al 2011), and delays Parkinson's disease-like symptoms induced by MPTP in non-human primates (Quik et al 2006). Recently it has been suggested that nicotine protection against MPTP in a mouse model of Parkinson's disease is via inhibition of astrocyte activation (Liu et al 2012).…”
Section: 0 Neuroprotectantsmentioning
confidence: 99%
“…In-vivo and in-vitro studies have shown that nicotine protects against nigrostriatal damage induced by various compounds. For example, in Parkinson's disease cell models nicotine protects against endogenous substances such as salsolinol and aminochrome that selectively damage dopaminergic cells (Copeland et al 2005, 2007; Das and Tizabi 2009; Muñoz et al 2012; Ramlochansingh et al 2011), and delays Parkinson's disease-like symptoms induced by MPTP in non-human primates (Quik et al 2006). Recently it has been suggested that nicotine protection against MPTP in a mouse model of Parkinson's disease is via inhibition of astrocyte activation (Liu et al 2012).…”
Section: 0 Neuroprotectantsmentioning
confidence: 99%
“…Enzymatic GSH conjugation of dopamine o-quinone to 5-S-glutathionyl dopamine was catalyzed by GSTM2, although a non-enzymatic reaction has also been reported [43,55]. In contrast, other studies have involved aminochrome formation prior to the experiment [56] or the use of purified aminochrome [57][58][59][60][61][62]; thus, it is possible that 5,6-indolequinone had been formed in these experiments. However, the aminochrome conjugation with glutathione catalyzed by glutathione S-transferase M2 (GSTM2) generated only 4-S-glutathionyl-5,6-dihydroxyindoline and not 4-S-glutathionyl-5,6-dihydroxyindole, which should be the product of 5,6-indolequinone glutathione conjugation [63].…”
Section: Dopamine Oxidation To Ortho-quinonesmentioning
confidence: 95%
“…The depletion of NADPH results in a decrease in reduced glutathione because NADPH is required for the enzymatic reduction of glutathione. Several reports demonstrate that the one-electron reduction of aminochrome is a neurotoxic reaction both in cell cultures and in vivo [27,28,32,33,54,[56][57][58][59][60][61][62][81][82][83][84][85][86].…”
Section: One-electron Reductionmentioning
confidence: 99%
“…Moreover, in vitro and in vivo studies have shown that nicotine may protect against nigrostriatal damage induced by various compounds. Thus, in Parkinson’s disease cell models, nicotine protects against endogenous substances such as salsolinol and aminochrome that selectively damage dopaminergic cells (Copeland et al 2005, 2007; Das and Tizabi 2009; Ramlochansingh et al 2011; Munoz et al 2012). Similarly in animal studies, including non-human primates, it has been shown that nicotine delays Parkinson’s disease-like symptoms induced by MPTP (Quik et al 2006, 2009, 2014).…”
Section: Nicotinementioning
confidence: 99%